Comparing Pathways into the Labor Market of Young People with Disabilities in Switzerland and Luxembourg - Justin Powell; Andeas Hadjar; Robin Samuel; Boris Traue; Carmen Zurbriggen (sozialpolitik.ch)
This Forum contribution, instead of following typical research article format, provides selected insights from the PATH_CH-LUX project on school-to-work transitions of young people with disabilities in Switzerland and Luxembourg, which examines drivers and barriers using a cross-national, mixed-methods approach. The project focuses on three perspectives: young people’s experiences, expectations, aspirations; employer recruitment practices analyzed through a factorial survey design; and insights from social service professionals to identify areas for improved transition support. Comparative institutional analysis highlights opportunity structures shaped by systemic factors in both countries. Preliminary findings from the authors’ research provide a foundation for understanding institutional, organizational, and individual factors affecting labor market inclusion. Both countries’ high-skill labor markets and multicultural contexts offer valuable cases emphasizing the need for the transformation of historically separate and stigmatizing educational settings, enhanced guidance and support systems,  employer awareness to improve experiences and outcomes for young people with disabilities transitioning school to work.